The influence of competence, compensation, and work ethics on employee performance at the department of communication, informatics, encryption, and statistics of serang regency - Ratu Namira Maulina; Khusnul Khotimah; Yayu Surati; John Chaidir; Haerofiatna Haerofiatna (Institute of Computer Science (IOCS), 2026)
This study aims to look at how competence, pay, and work ethic affect employee performance at the Department of Communication, Informatics, Encryption, and Statistics in Serang Regency. The research used a quantitative method, gathering data through questionnaires, direct observations, and document reviews. A total of 75 employees took part as respondents, chosen using a census sampling method to ensure all parts of the group were included. The data was then processed and analyzed using multiple linear regression to understand how the different factors relate to each other. The results show that employee competence has a positive and significant impact on performance, meaning that having more knowledge, skills, and abilities leads to better job results. However, pay was not found to have a significant effect on performance, implying that current salary structures might not be a major driver for improvement. Work ethic, on the other hand, had a positive and significant effect, highlighting the role of values like discipline, responsibility, and dedication in achieving good performance. When all three factors—competence, pay, and work ethic—are considered together, they have a significant combined effect on performance. These findings suggest that improving employee competence and promoting a strong work ethic is important, and that organizations should consider reviewing their pay systems. The study offers useful information for enhancing human resource management in public sector organizations